Principle Of "Secularity" And Its Interpretations - Kasimova Zumrad (Zien Journals, 2022)
In this article, the principle of "secularism" and its interpretations are comparatively analyzed, and the influence of the relations between the state and religion in the conditions of a democratic state is discussed
Keywords: religion; secularism; religiosity; state